Partial dielectric behavior of the Mo electron spectrum as an effect of Van Hove singularities - Ignatyeva, Т.А. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2011)
The investigation shows that the specific conductivity of Mo sharply decreases exponentially under the temperature influence within the range from ~20 to ~60 K or under the Re impurity influence in the concentration range up to 3  4 at.% and then transforms into the power dependence. Noted there are two singularities in the Mo specific conductivity, namely, an exponential conductivity change within the small energy range and the presence of a threshold energy value equivalent to ~50 K, which can be related to the mobility edge for localized electron states at the spectrum edge in the vicinity of the critical energy C1 (arising of a small-size electron lens). The identity in the behavior of Mo specific conductivity change, independently on the external parameter influencing on the Fermi level position relatively to the critical points of the electron spectrum, is shown. This fact permits to assume that the singularities under consideration can be related to the partial dielectric behavior of the electron spectrum, depending on the Fermi level position relatively to the critical energies